Concise history of western music - Hanning, Barbara Russano, 1940- 4 0 16; (James Peter). Burkholder, J. Peter; 5 (New York : W.W. Norton, 2006)
Chronicles the history of Western music from ancient Greece and Rome through the post-World War II era, and includes sidebars, illustrations, music examples, and a glossary.
Based on J. Peter Burkholder, Donald J. Grout and Claude V. Palisca, A history of western music, seventh edition.
Includes bibliographical references and index.
Adult;Adult.
Keywords: 2 -- 0; 6; History and criticism. -- Music -- 20; 20; 2